Frequency of complications in ultrasound-guided percutaneous nephrostomy: an analysis using the modified clavien classification system - Iqbal, Muhammad Danial; Ahmed, Mushtaq; Waleed , Ahmad; Tanzeel-Ur-Rahman Gazder; Rabiullah , Syed; Saad, Hafiz Muhammad (Journal of the Pakistan Medical Association, 2025)
Objective: To determine the frequency of complications following percutaneous nephrostomy using the Modified Clavien Classification System in patients with urinary tract obstruction in a tertiary care setting. Method: The observational study was conducted at the Department of Urology, Sindh Institute of Urology and Transplantation, Karachi, from August 18, 2022, to February 17, 2023, and comprised individuals of either gender aged 16-70 years who were experiencing different types of urinary tract obstructions. The patients were subjected to percutaneous nephrostomy, and they were monitored for 15 days after the surgery. Complications post-procedure were noted using the Modified Clavien Classification System. Data was analysed using SPSS 26. Results: Of the 90 patients with mean age 50.19±14.70 years, 53(58.9%) were males and 37(41.1%) were females. Grade I complications were observed in 37(41.1%) cases, grade II 8(8.9%), grade IIIa 11(12.2%), and grade IVa in 1 (1.1%) case. No complications were observed in 33(36.7%) cases. Complications were not significantly associated with age, gender, body mass index, site of insertion and comorbidities (p>0.05). Conclusion: The most common complication observed in patients with urinary tract obstruction was grade I, followed by grade IIIA, while grade IVA had the least common incidence. Key Words: Clavien classification, Complication, Percutaneous Nephrostomy, Urinary tract obstruction.